Effects of straw management on rice productivity in northern Uganda - Apiou, David; Echaku, Samuel; Barakagira , Alex; Ocwa, Akasairi; Bua, Bosco (Acta Agraria Debreceniensis, 2026)
Rice (Oryza sativa L.) is an important crop regarding food security worldwide. However, straw management is an important practice with a pronounced effect on the subsequent production cycle. The objective of the study was to determine the effects of straw management on rice genotype productivity in northern Uganda. Randomized complete block arranged as split plots experiments with three replications were conducted in 2021 and 2022 seasons, with two treatments including rice straw incorporation (RRI) and removal (RRR) Two rice varieties; PR107 and NamChe 5 were included in the study. The results showed that grain yield was significantly influenced by variety (P